Pengaruh Media Lagu Isi Piringku Terhadap Pengetahuan Dan Sikap Tentang Gizi Seimbang Pada Anak Min 2 Kota Bengkulu - Haredika, Afdeo Fitra; Marleni, Wisuda Andeka; Marsofely, Reka lagora (Poltekkes Kemenkes Bengkulu, 2022)
There is still a serious issue regarding nutrition in Indonesia. Numerous health problems arise due to alackofunderstanding of balanced nutrition, and this can af ect various age groups, including schoolchildren. Childrenwholack proper nutrition may experience obstacles in physical, mental, and intellectual growth. This researchaimstoassess the impact of using media, specifically the